Inventory and Diversity of Associated Mangrove Species in the Cemare Mangrove Forest Area, South Lembar - Fathurrahman, Lalu Arip; Handayani, Baiq Sri; Suyantri, Eni (Jurnal Biologi Tropis, 2026)
The coastal area of West Lombok possesses high biodiversity, yet the existence of associated mangroves, which play a crucial ecological role as natural buffers and carbon sinks, is frequently overlooked. This study aims to identify and inventory the associated mangrove species in the Cemare Mangrove Forest, South Lembar, West Lombok. The research was conducted from October to November 2025. Inventory data were collected using the quadrat transect method across three stations, selected through a purposive sampling technique based on environmental conditions. The results demonstrated a high level of biodiversity, recording a total of 1,321 individuals comprising 20 species. All identified species are classified into 3 divisions, 4 classes, 11 orders, and 12 families. The highest composition was contributed by Sporobolus virginicus 29.30%, Sesuvium portulacastrum 28.31%, and Clerodendrum inerme 13.70% of the total individuals, with a distribution pattern spanning both revegetation and natural vegetation areas. Ecologically and economically, associated mangroves offer significant benefits, such as serving as natural coastal protection against abrasion and as potential sources for medicine. Therefore, the conservation of associated mangrove species is highly essential due to its positive impacts. This inventory data will serve as a baseline database for sustainable conservation and holds great potential to support the development of marine ecotourism.